Mafhum al-zulm fi dhaw'i al-Quran al-Karim - Siti Khadijah Bt Hamid (Universiti Sains Islam Malaysia, 2014)
The research title is "The meaning of cruel according from Quran". It's divided to three chapters and the methodology of research is through library research and took information from internet. The aim of this project is to explain about the truth meaning of cruel according from Quran. As we know, the most popular meaning of cruel is put something not at their place. However. in this research I'll try to explain various of cruel meanings. In this research we will find out more words of cruel in Quran. Thus, we also find out the difference meaning about cruel. The truth that, cruel is bad behavior. So, we as Muslim people must avoid this behavior and forbade this among people.